Optimizing Propylene Glycol Purity and Profitability through Variations in Reactor Temperature and Distillation - Klara Dwi Ajeng Anditariani; Dea Arum Dwi Lestari; Jesica Fernanda Putri; Lilia Hasna Fauzia; Puspa Sandra Prastica (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Propylene glycol (PG) is a multifunctional diol widely used in food, pharmaceutical, cosmetic, and chemical industries due to its favorable physicochemical properties, high water solubility, and low toxicity. This study examines PG production through non-catalytic hydration of propylene oxide, focusing on the effect of reactor inlet temperature on process efficiency and economic performance. In the process, propylene oxide and water are mixed and fed into a continuous stirred-tank reactor (CSTR), followed by distillation for product purification. Temperature variations from 23.9 °C to 80 °C were analyzed to determine their impact on conversion and profitability. At 23.9 °C, the process was economically unfavorable, yielding a negative profit of –161.09 /hour. Increasing the inlet temperature to 40 °C significantly improved conversion and distillation efficiency, resulting in a profit of 191.09 /hour (552,689 /year). Further temperature increases provided no additional economic benefit and increased energy demand. Therefore, 40 °C is recommended as the optimal operating condition, offering the best balance between technical performance and profitability. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).